Risk Management of Cost Escalation in Construction Projects During the Reform of the Pricing System - Dankevych, Nataliia; Arutiunian , Iryna (Ways to Improve Construction Efficiency, 2025)
The article examines the challenges of managing the risks of cost escalation in construction projects in the context of reforming the pricing system in Ukraine. The relevance of the study is driven by the need to improve the effectiveness of construction project management in an unstable economic and regulatory environment. The main objective of the study is to substantiate effective approaches to managing the risks of rising construction project costs under conditions of pricing system reform, ensuring the minimization of unforeseen expenses, improved accuracy of cost estimation, and the financial stability of construction companies. The study includes a comprehensive analysis of current scientific publications, regulatory documents, and reports, as well as a synthesis of practical experience in applying innovative methods and models in both domestic and international construction practice. The impact of dynamic changes in the regulatory framework, price volatility of construction materials and energy resources, and constraints caused by martial law on the effectiveness of project planning and implementation is analyzed. Particular attention is paid to the need to adapt traditional risk management methods to today’s unstable environment, improve the accuracy of cost calculations, and ensure the financial stability of companies. Approaches to flexible and transparent construction cost formation are proposed, which contribute to minimizing unforeseen expenses and increasing client confidence. The results indicate that modern methods of managing construction cost escalation risks, combined with the reform of the pricing system, make it possible to improve the accuracy of cost planning, minimize unforeseen expenses, and ensure the financial stability of companies.